Risk of Venous Thromboembolism Following Rhinoplasty. (3rd January 2021) - Okland, Tyler S; Wadhwa, Harsh; Patel, Priyesh N; Most, Sam P
Abstract: Background: Although prior studies have identified a low risk of venous thromboembolism (VTE) in rhinoplasty, these studies are limited by small samples and associated risk factors remain unknown. Objectives: The aim of this study was to discern the incidence of VTE following rhinoplasty in a large patient population through analysis of a nationwide insurance claims database. Methods: This study involved a population-based retrospective analysis of insurance claims made by patients who underwent rhinoplasty between 2007 and 2016. Established risk factors for VTE, demographic data, procedural details, and absolute incidence of VTE were collected. Results: We identified a total of 55, 287 patients who underwent rhinoplasty from 2007 to 2016. Mean age [standard error of the mean] was 38.74 [0.06] years (range, 18-74 years), and 54% were female. The overall incidence of VTE was 111, of which 70 were DVT and 41 were PE. From multivariate regression analysis, previous VTE (odds ratio [OR], 52.8; 95% confidence interval [CI], 35.2-78.6; P  < 0.0001), peripherally inserted central catheter (PICC)/central line placement (OR, 19.6; 95% CI, 9.8-153; P  < 0.05), rib graft (OR, 4.6; 95% CI, 2.3-8.5; P  < 0.0001), age 41 to 60 years (OR, 2.65; 95% CI, 1.7-4.3; P  < 0.01), inflammatory bowel disease (IBD) (OR, 2.6; 95% CI, 1.0-5.5; P  < 0.05), and age 61 to 74 years (OR, 2.4; 95% CI, 1.2-4.8; P  < 0.05) were associated with an increased risk of VTE. Conclusions: We demonstrate a low overall incidence of VTE in rhinoplasty patients. Previous VTE, PICC/central line, advancing age, IBD, and intraoperative rib graft harvest were most strongly associated with VTE in this population cohort. Level of Evidence: 4: